2017
DOI: 10.2196/medinform.6226
|View full text |Cite
|
Sign up to set email alerts
|

Applying STOPP Guidelines in Primary Care Through Electronic Medical Record Decision Support: Randomized Control Trial Highlighting the Importance of Data Quality

Abstract: BackgroundPotentially Inappropriate Prescriptions (PIPs) are a common cause of morbidity, particularly in the elderly.ObjectiveWe sought to understand how the Screening Tool of Older People’s Prescriptions (STOPP) prescribing criteria, implemented in a routinely used primary care Electronic Medical Record (EMR), could impact PIP rates in community (non-academic) primary care practices.MethodsWe conducted a mixed-method, pragmatic, cluster, randomized control trial in research naïve primary care practices. Phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 41 publications
(54 reference statements)
1
49
0
2
Order By: Relevance
“…Similar to other reported findings [ 17 , 19 , 31 , 32 ], we identified data quality issues in the MUSIC EMR data set that limit confidence in the use of chronic disease data for practice-based initiatives and research. Previous research in problem list design identified the benefit of incorporating the problem list into the clinical documentation routine [ 18 , 26 ]; this need was echoed in the feedback from MUSIC clinicians that were consulted in the design of the EMR interface improvement.…”
Section: Discussionsupporting
confidence: 80%
“…Similar to other reported findings [ 17 , 19 , 31 , 32 ], we identified data quality issues in the MUSIC EMR data set that limit confidence in the use of chronic disease data for practice-based initiatives and research. Previous research in problem list design identified the benefit of incorporating the problem list into the clinical documentation routine [ 18 , 26 ]; this need was echoed in the feedback from MUSIC clinicians that were consulted in the design of the EMR interface improvement.…”
Section: Discussionsupporting
confidence: 80%
“…Data quality in electronic health records (EHRs), particularly completeness of reporting, is indispensable for the associated decision support components to prove effective. Poor reporting observed in this project were similarly observed in a recent trial incorporating the Screening Tool of Older People’s Prescriptions prescribing criteria in a primary care EHR, which demonstrated the need for continued assessment of data quality and improvement on potentially inappropriate prescription rates in community primary care settings [ 22 ]. A 2013 study of implementation of national guidelines and an associated structured type 2 diabetes and hypertension patient record reported poor use of structured record by providers as a primary explanation for null benefit of the intervention [ 23 ].…”
Section: Discussionmentioning
confidence: 79%
“…Recommendations for future research related to the STOPP criteria include embedding it within CDS tools in electronic health records, as a means to improve efficiency during the screening process. 37 Combining use of the STOPP criteria with, or comparing it with, other screening tools such as the Beers Criteria or the Medication Appropriateness Index could improve clinical appropriateness. 38 Unutmaz et al 34 have recommended that future research examine the long-term clinical effects of using the STOPP criteria to reduce inappropriate medications and reduce ADEs.…”
Section: Discussionmentioning
confidence: 99%